Das "friedliche Atom" als Narrativ in Politik, Wissenschaft und Design Ikonografie eines Diskurses zwischen 1953 und 1978 - Gantner, Manuela (KIT Scientific Publishing, 2023)
The work deals with the iconography of the atom from the euphoria about nuclear technology of the 1950s to the anti-nuclear movement of the 1970s in the Federal Republic of Germany. Using the life and work of the German architect and graphic designer Rolf Lederbogen as an example, the socio-political dimension of nuclear technology in communication and visualisation of the narrative "Atoms for Peace" is put in context with the history of technical thinking in architecture and design.